The Effect of Corporate Social Responsibility on Financial Performance in Chemical Industry Companies Listed in IDX - Arisandy, Maya; Amrulloh, Ihsan; Ghifari Arkan, Muhammad (Accounthink : Journal of Accounting and Finance, 2024)
The financial performance of Chemical Industry companies in 2019-2021 as measured by Return on Assets, Return on Equity, and Return on Sales, there were increases and decreases. This can happen due to several factors such as fluctuations in raw material prices and the emergence of the Covid-19 outbreak. Financial performance is a factor that provides freedom and flexibility to management to carry out and disclose Corporate Social Responsibility (CSR) programs. The purpose of this research is to determine the influence of Corporate Social Responsibility on company financial performance. Proxies for financial performance are Return on Assets, Return on Equity, and Return on Sales. The indicators used by Corporate Social Responsibility are based on the GRI (Global Reporting Initiatives) version G4 indicators. This research uses Chemical Industry companies on the Indonesia Stock Exchange (BEI) in 2019-2021. The method used in this research is a quantitative method. The population in this research is Chemical Industry companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The research sample was determined using a purposive sampling method so that 13 companies were obtained as samples. The research results show that Corporate Social Responsibility has an effect on Return on Equity, but has no effect on Return on Assets and Return on Sales.